Islam dan Kebijakan Negara dalam Perlindungan terhadap Hak Reproduksi Pekerja Perempuan pada Keluarga Muslim - Rendy Dwi Hermanto; Sheyla Nichlatus Sovia (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The position of women is clear both in terms of Islamic perspective and in terms of state policies in the form of laws and regulations that have placed women in a dignified position that can develop themselves in carrying out their roles, duties and functions. On the other hand, participating in maintaining a balance between family responsibilities and work outside the household without neglecting roles in the household and maintaining social and religious culture values. The existence of women workers cannot be denied, both on a large scale role in the development of the nation and state as well as on the scale of status and family welfare by working outside the home (productive work) or social activities in irder to actualize themselves. This research seeks to find a tangent point between Islamic teachings and state policies in providing protection for the reproductive rights of female workers. The results of the study show that the concepts contained in Islamic teachings and state policies have many tangent points related to the obligation to provide protection for workers, especially female workers and the fulfillment of their rights for the benefit of mankind as a whole.